2021
DOI: 10.1016/j.adolescence.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent depressed mood and difficulties with emotion regulation: Concurrent trajectories of change

Abstract: Introduction: Adolescent depression is a signiicant mental health concern. Emotion regulation dificulties have been associated with subsequent depressive symptoms, though different facets of emotion regulation are rarely compared. This study examined the degree to which trajectories of change in different facets of emotion regulation (goal-directed behavior, impulse control, and regulation strategies) and depressive symptoms were associated across twelve months in a clinical adolescent sample. Methods: Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 100 publications
1
6
0
Order By: Relevance
“…These changes can reduce stress, enhance positive emotional experience, improve impulse control ability, and finally improve emotional regulation and depressive symptoms. These findings also explain the conclusions of Annamarie et al from a physiological level ( Defayette et al, 2021 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These changes can reduce stress, enhance positive emotional experience, improve impulse control ability, and finally improve emotional regulation and depressive symptoms. These findings also explain the conclusions of Annamarie et al from a physiological level ( Defayette et al, 2021 ).…”
Section: Discussionsupporting
confidence: 89%
“…The improvement of emotional regulation and depression in the experimental group may be related to the improvement of impulse control ability. Annamarie et al found that enhancing impulse control ability was a key factor in the treatment of depression ( Defayette et al, 2021 ). Our findings also indicated that GIMT may be more suitable for the emotional expression characteristics of girls as the improvement of impulse control, total emotional regulation, and depression of girls were significantly higher than those of boys in the experimental group.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study of 390 adolescents, for example, showed that self-efficacy beliefs about negative emotion regulation were related to depression both concurrently and across time, up through age 20 (Caprara et al, 2010). Other research with adolescents ( M age = 15) enrolled in a randomized controlled trial found that as the perceived ability to control impulses improved, depressive symptoms decreased (Defayette et al, 2021). The ability to regulate negative emotions and self-efficacy beliefs tied to an individual’s skill in doing so are important parts of adolescent development.…”
Section: Regulatory Emotional Self-efficacy Social Support Internaliz...mentioning
confidence: 99%
“…Emotion dysregulation refers to the inability to identify, understand, and manage one's own emotions in an adaptive way (10,11). Several studies have suggested that emotion dysregulation plays a significant role in developing and maintaining depression and suicide-related behaviors in adolescents (12)(13)(14), which confers prospective vulnerability to psychopathology in adulthood. However, existing studies have predominantly focused on examining emotion dysregulation as a broad risk factor for suicidal behavior, overlooking the potential neurobiological underpinnings of suicide, especially alterations in brain functioning as detected through imaging techniques (15, 16).…”
Section: Introductionmentioning
confidence: 99%